Islamic Banking's Decades-Long Institutionalisation Struggle: The Case of Pakistan - Ashfaq Khan (Australasian Accounting, Business and Finance Journal, 2024)
Islamic Banking (IB) still struggles to institutionalise its practices at the wider societal level. The literature, despite having covered the sector from several angles, has overlooked an objective evaluation of the root causes of its restricted institutionalisation so far. This empirical investigation into Pakistan's IB sector fills this void and investigates the sector's apparent limited success in institutionalising its practices despite having been formally accorded legitimate legal status around the world. The paper, bringing the sector's governance to the spotlight, concludes that the social practice's 'site' of development – the Islamic Shari'ah jurisprudence, has too strong a coupling of internal elements to accommodate the sector's current loose adherence to its principles and laws, and thus the sector, rather than its 'site' of its development, needs to adapt and reorient to accomplish unrestricted institutionalisation. The paper also extends Foucault's theoretical constructs in the sector's peculiar context, which stems from a unique cultural, economic, and regulatory environment. The paper aims to add a new dimension to the IB governance literature and help steer future research focus to areas with the highest marginal utility for the sector and its stakeholders.
Keywords: Islamic banking; institutionalization; institutionalisation; compliance with Shari’ah; site of the social; Pakistan